Effect of Magnesium Incorporation on Solution-Processed Kesterite Solar Cells - Caballero, Raquel; Haass, Stefan G.; Andres, Christian; Arques, Laia; Oliva, Florian; Izquierdo-Roca, Victor; Romanyuk, Yaroslav E. (Frontiers in Chemistry, 2018)
The introduction of the alkaline-earth element Mg into Cu2ZnSn(S,Se)4 (CTZSSe) is explored in view of potential photovoltaic applications. Cu2Zn1-xMgxSn(S,Se)4 absorber layers with variable Mg content x=0…1 are deposited using the solution approach with dimethyl sulfoxide solvent followed by annealing in selenium atmosphere. For heavy Mg alloying with x = 0.55…1 the phase separation into Cu2SnSe3, MgSe2, MgSe and SnSe2 occurs in agreement with literature predictions. A lower Mg content of x=0.04 results in the kesterite phase as confirmed by XRD and Raman spectroscopy. A photoluminescence maximum is red-shifted by 0.02 eV as compared to the band-gap and a carrier concentration NCV of 1 x 1016 cm-3 is measured for a Mg-containing kesterite solar cell device. Raman spectroscopy indicates that structural defects can be reduced in Mg-containing absorbers as compared to the Mg-free reference samples, however the best device efficiency of 7.2% for a Mg-containing cell measured in this study is lower than those frequently reported for the conventional Na doping.